Histidine N(τ)-cyclized macrocycles as a new genre of polo-like kinase 1 polo-box domain-binding inhibitors. Issue 19 (15th October 2018) - Hymel, David; Grant, Robert A.; Tsuji, Kohei; Yaffe, Michael B.; Burke, Terrence R.
Graphical abstract: Highlights: Peptide macrocyclization is an important step in advancing peptides to peptidomimetics. Size reduction of Plk1 PBD-binding peptides with retention of affinity is desired. Histidine N(τ)-cyclized macrocyclization has resulted in a tripeptide with high affinity. Abstract: Transition toward peptide mimetics of reduced size is an important objective of peptide macrocyclization. We have previously shown that PLH ∗ SpT (2a ) (where H ∗ indicates the presence of a –(CH2 )8 Ph group at the N(π) position and pT indicates phosphothreonine) is an extremely high affinity ligand of the polo-like kinase 1 (Plk1) polo-box domain (PBD). Herein we report that C -terminal macrocyclization of2a employing N(π), N(τ)-bis-alkylated His residues as ring junctions can be achieved in a very direct fashion. The resulting macrocycles are highly potent in biochemical assays and maintain good target selectivity for the Plk1 PBD versus the PBDs of Plk2 and Plk3. Importantly, as exemplified by5d, our current approach permits deletion of the N -terminal "Pro-Leu" motif to yield tripeptide ligands with decreased molecular weight, which retain high affinity and show improved target selectivity. These findings could fundamentally impact the future development of peptide macrocycles in general and Plk1 PBD-binding peptide mimetics in particular.